Bereavement, Loss and Learning Disabilities : a Guide for Professionals and Carers - Grey, Robin, 1962- (Jessica Kingsley Publishers, 2010)
Losing a loved one and coping with the subsequent adjustments that follow are a difficult fact of life, but people with learning disabilities face specific difficulties in processing and managing these changes. Adopting an integrative approach, this book acknowledges the importance of helping relationships in supporting this vulnerable group through periods of loss and bereavement. The author explains how to engage the person with a learning disability in talking therapy by creating an open dialogue. Common signs of stress, factors to consider in assessing risk and advice on how best to approa.